Cytotoxic, Antioxidant, and Antidiabetic Activities versus UPLC-ESI-QTOF-MS Chemical-Profile Analysis of Ipomoea aquatica Fractions - Hefny Gad, Mahmoud; Demeyer, Kristiaan; Vander Heyden, Yvan; Mangelings, Debby (Planta Medica, 2021)
Ipomoea aquatica is a common green leafy vegetable that has numerous uses in traditional medicine. This study focused on the determination of the cytotoxic, antiradical, and antidiabetic properties of various fractions of the I. aquatica methanolic extract, as well as on the tentative identification of some bioactive compounds in the same fractions. The cytotoxicity was determined by the brine shrimp lethal test. The antioxidant activities of the I. aquatica fractions were investigated through 3 assays. The antidiabetic activity (in vitro) was measured by α-glucosidase and α-amylase inhibition assays. Phytochemical qualitative analyses demonstrated the presence of alkaloids, terpenoids, phenols, and flavonoids in the ethyl acetate-methanol and methanol fractions. The total phenolic and total flavonoid contents were found to be highest in the ethyl acetate-MeOH fractions. The evaluation of the cytotoxicity showed that the hexane-dichloromethane fraction is the most toxic, while the others are moderately toxic. The antioxidant activity assays showed that the ethyl acetate-MeOH fractions are the most potent, while the α-glucosidase and α-amylase assays revealed that the hexane-dichloromethane fraction might contain a potent antidiabetic agent. Some bioactive substances in the MeOH fractions, such as salicylic acid glucoside, 1-O-sinapoyl-β-D-glucose derivative, and dihydroferulic acid derivative, were tentatively identified. To the best of our knowledge, this is the first report to detect and identify these compounds in this species. Based on the results of this study, it may be concluded that I. aquatica is a potent antioxidant agent and could be a good candidate as a natural antioxidant in food and therapeutics.
Keywords: Ipomoea aquatica; Convolvulaceae; chemical-profile analysis; cytotoxic activity; antioxidant activity; antidiabetic activity